2018
DOI: 10.1002/lsm.23008
|View full text |Cite
|
Sign up to set email alerts
|

Acne vulgaris severity graded by in vivo reflectance confocal microscopy and optical coherence tomography

Abstract: Combined use of RCM and OCT elucidated distinctive follicle infundibulum characteristics and inflammation degree that were associated with acne severity. Future trials may apply imaging techniques to support clinical acne grading, and monitor treatment efficacy. Lasers Surg. Med. 9999:1-10, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(88 citation statements)
references
References 29 publications
1
87
0
Order By: Relevance
“…RCM and OCT have previously been used to explore acne and healthy skin morphology . Overall, the studies found that hair follicles of acne patients were enlarged with hyperkeratinized borders and sebum plugs compared to healthy skin follicles.…”
Section: Introductionmentioning
confidence: 98%
“…RCM and OCT have previously been used to explore acne and healthy skin morphology . Overall, the studies found that hair follicles of acne patients were enlarged with hyperkeratinized borders and sebum plugs compared to healthy skin follicles.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the numerous types of lesions in dermal inflammatory diseases, the external appearance and subcutaneous morphology of the lesions may aid in distinguishing lesion type . A study using OCT has been able to identify morphological variances in pustules of Malassezia fungi (MaF), a folliculitis often mistaken for acne due to its similar dermal appearance .…”
Section: Discussionmentioning
confidence: 99%
“…Although histopathology is considered the optimal method to study the morphological changes associated with acne, it is not feasible for an in vivo follow‐up of the same lesion during time. Recently, Reflectance Confocal Microscopy (RCM) and Dynamic Optical Confocal Microscopy (D‐OCT) have been applied to the non‐invasive exploration of acne at a microscopic resolution . Previous studies demonstrated that, compared to healthy individuals, the pilosebaceous units of the clinically unaffected skin of acne patients showed larger infundibular diameter, with bright border and amorphous material inside, whilst the pilosebaceous units of healthy patients showed well‐defined, roundish/elliptic infundibula, that did not contain amorphous or bright material .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Reflectance Confocal Microscopy (RCM) and Dynamic Optical Confocal Microscopy (D-OCT) have been applied to the non-invasive exploration of acne at a microscopic resolution. [13][14][15][16] Previous studies demonstrated that, compared to healthy individuals, the pilosebaceous units of the clinically unaffected skin of acne patients showed larger infundibular diameter, with bright border and amorphous material inside, whilst the pilosebaceous units of healthy patients showed well-defined, roundish/elliptic infundibula, that did not contain amorphous or bright material. 13,17 Furthermore, D-OCT imaging enables to identify the alterations of the microcirculation providing information on the dermal blood flow, which is of great value in the characterization of the inflammatory process and in the determination of the functional and metabolic features of skin diseases.…”
Section: Introductionmentioning
confidence: 99%